Calotropis procera: A Browsing Record of alternate Food Choice by Blackbucks in Western Haryana, India - Delu, Vikram; Singh, Dharambir; Dookia, Sumit; Priya; Karwasra, Vinod (Indian Forester, 2022)
During the present investigation, the first browsing record on the leaves of Calotropis procera by blackbucks have been reported from the two populations (Badopal and Mangali Surtia) of semi arid ecosystem in Western Haryana, India. The fortnightly visits were conducted to record the diurnal data of food preferences using Scan sampling from September 2019 to August 2020 at Badopal and consequently record was confirmed from Mangali Surtia. Out of a total of 53 floral species documented from the Badopal site, blackbucks consumed 26 plant species belonging to 25 families with varied degree of preferences according to availability and selectivity. Present study showed that the blackbucks are selective feeder and in scarcity of food they can be shifted from grazing to browsing habit and observed to consume Calotropis procera, as an alternate food choice during lean period of time, which is generally not eaten by herbivores due to its chemical mechanism. C. procera has enormous properties for its medicinal uses, therefore, based upon our observation in wild, it is suggested that leaves of Calotropis can be supplemented with other feed in captive ruminates like blackbucks and other ungulates in India to complete their therapeutic need.